AB0707 Initial Limited Three-Level Thin-Section Computed Tomography Scorings Predict the Prognosis of Acute/Subacute Interstitial Pneumonia in Patients with Dermatomyositis. (9th June 2015) - Konma, J.; Kotani, T.; Ishida, T.; Oda, K.; Isoda, K.; Hata, K.; Yoshimatsu, Y.; Takeuchi, T.; Makino, S.; Hanafusa, T.
Abstract : Background: Interstitial pneumonia (IP) is a common complication of dermatomyositis (DM), causing increased morbidity and mortality. DM with acute/subacute IP (A/SIP) progresses rapidly and the prognosis is poor. Previous studies have reported the following adverse prognostic factors: high initial serum ferritin level, high alveolar arterial oxygen gradient (AaDO2 ), low vital capacity, negative anti-aminoacyl tRNA synthetase (ARS) antibody, and positive anti-melanoma differentiation associated gene (MDA) 5 antibody. It is crucial to enable early prognosis prediction at the time of DM-A/SIP diagnosis. Objectives: We examined to predictable of the prognosis from chest high-resolution computed tomography (HRCT) image of DM/A/SIP. Methods: Data were obtained retrospectively from medical records of 20 consecutive DM-A/SIP patients admitted to Osaka Medical College Hospital and Yodogawa Christian Hospital between July 2011 and January 2014. Chest HRCT images were reviewed by 3 independent observers blinded to clinical information, and quantified using the CT score including both ground-glass opacity (GGO) score and fibrosis score as defined by Kazerooni. Each patient's lobe was scored by same observers and using the average value. Briefly, limited 3 CT levels were pre-selected: aortic arch, the carina, and 1 cm above the diaphragm. Each lobe (right upper, middle, and lower, and left upper and lower lobes) of the lung was scored at the 3 sites on a scale of 0-5. Results: Of the 20 patients, 7 died of IP. No significant differences were observed in patients background excluding anti-ARS antibody positivity and anti-MDA 5 antibody positivity between survivors and those who died. No significant differences were observed in chest HRCT findings between them. GGO scores in both upper lobes and the right middle lobe were significantly higher in the fatalities (P=0.01, 0.001, 0.02), but there was no significant difference in both lower lobes. Fibrosis scores in the right middle lobe was significantly higher in the fatalities (P=0.02), but there was no significantly difference in other lobes. A right middle lobe GGO score of ≥3 was determined as the best cut-off value for a poor prognosis (sensitivity: 85.7%, specificity: 85.7%), and the survival rate after 24 weeks was significantly lower in patients with a right middle lobe GGO score of ≥3 (survival rate: 0.0%) than in those with <3 (92.9%) ( P <0.0001). Conclusions: Initial limited three-level thin-section CT scorings may be a useful prediction marker of DM-A/SIP. Acknowledgements: Takao Kamimori, Hiroshi Fujiwara, Yodogawa Christian Hospital Disclosure of Interest: None declared